A review of the anesthetic implications of marijuana use. Issue 3 (3rd July 2019) - Alexander, John C.; Joshi, Girish P.
Abstract: Marijuana, derived from plants of the genus Cannabis, is the most commonly used illicit drug in the United States. Marijuana is illegal at the federal level and remains a Drug Enforcement Agency Schedule 1 substance. Nevertheless, most states have passed less stringent legislation related to its use, ranging from decriminalization of possession to allowing medical or even recreational use, and some county and municipal law enforcement agencies have refrained from prosecuting personal possession and/or use even when statute would require such action. Therefore, as use of marijuana becomes more common in the larger population, more patients who are chronic and/or heavy users of marijuana present for surgical procedures, raising the question of best practices to care for these patients in the perioperative period. This review summarizes the known physiologic effects of marijuana in humans, discusses potential implications of marijuana use that the anesthesiologist should consider at each phase of the perioperative period, and outlines recommendations for future study.